In Vivo Assessment of Bone Regeneration in Alginate/Bone ECM Hydrogels with Incorporated Skeletal Stem Cells and Single Growth Factors. - David Gothard; Emma L Smith; Janos M Kanczler; Cameron R Black; Julia A Wells; Carol A Roberts; Lisa J White; Omar Qutachi; Heather Peto; Hassan Rashidi; Luis Rojo; Molly M Stevens; et al. (PLoS ONE)
The current study has investigated the use of decellularised, demineralised bone extracellular matrix (ECM) hydrogel constructs for in vivo tissue mineralisation and bone formation. Stro-1-enriched human bone marrow stromal cells were incorporated together with select growth factors including VEGF, TGF-β3, BMP-2, PTHrP and VitD3, to augment bone formation, and mixed with alginate for structural support. Growth factors were delivered through fast (non-osteogenic factors) and slow (osteogenic factors) release PLGA microparticles. Constructs of 5 mm length were implanted in vivo for 28 days within mice. Dense tissue assessed by micro-CT correlated with histologically assessed mineralised bone formation in all constructs. Exogenous growth factor addition did not enhance bone formation further compared to alginate/bone ECM (ALG/ECM) hydrogels alone. UV irradiation reduced bone formation through degradation of intrinsic growth factors within the bone ECM component and possibly also ECM cross-linking. BMP-2 and VitD3 rescued osteogenic induction. ALG/ECM hydrogels appeared highly osteoinductive and delivery of angiogenic or chondrogenic growth factors led to altered bone formation. All constructs demonstrated extensive host tissue invasion and vascularisation aiding integration and implant longevity. The proposed hydrogel system functioned without the need for growth factor incorporation or an exogenous inducible cell source. Optimal growth factor concentrations and spatiotemporal release profiles require further assessment, as the bone ECM component may suffer batch variability between donor materials. In summary, ALG/ECM hydrogels provide a versatile biomaterial scaffold for utilisation within regenerative medicine which may be tailored, ultimately, to form the tissue of choice through incorporation of select growth factors.